STUDI KELAYAKAN USAHA PEMBESARAN IKAN LELE DUMBO DI KELURAHAN GUNTUNG PAYUNG KOTA BANJARBARU - Inda Ilma Ifada; Ana Zuraida; Igit Supriadi (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2016)
Catfish is a species of freshwater fish are easier to develop and market opportunities are promising, addition catfish also have good taste, high nutritional content, and the price is relatively cheap so it has the potential to be developed. However, based on preliminary surveys and the information obtained is known that some fish farmers pay less attention to the procedures or techniques fish rearing African catfish correct and profitable. therefore, this study aims to determine the technical and economic aspects of the business of enlarging catfish in the Fish Farmers Group Guntung Umbrella Village District of Runway Ulin Banjarbaru. This research uses survey and purposive sampling method. Sample been 8 each group of farmers with a simple random sampling method. The results showed that the technical enlargement conducted intensive catfish, catfish seed stocked two to three times a year, carried out during the rainy season. Economic aspects of the business of enlarging catfish profitable and worth the effort because of the value of production and the selling price is above the BEP production value of 300 kg and BEP Rp. 14 603, - / kg and Revenue acquisition cost ratio (RCR) effort is 1.28.